ANALISIS RESOURCE BASED LEARNING TERHADAP PEMANFAATAN KOLEKSI PERPUSTAKAAN SEKOLAH SMAS NURUL AMALIYAH TJ. MORAWA - Raflika, Lili; Isnaini; Sari Harahap , Ulfa Hayana; Andini, Sari; Siregar , Fikri Hamdi (CV. Arsy Persada Quality, 2024)
This research aims to investigate the effect of utilizing the SMAS Nurul Amaliyah Tj school library collection. Morawa through a Resource-Based Learning (RBL) approach to student learning at the upper secondary education level. Qualitative research methods were used, involving observation, interviews and document analysis as data collection techniques. Research participants consisted of students and library staff who were selected purposively. The research results show that students actively use a variety of library resources, both print and digital, to support their learning. There are varying usage dynamics, reflecting different preferences and learning styles among students. Students' experiences and perceptions highlight the benefits of easy access to information and support in the development of information literacy skills. The role of library staff is also recognized as an important factor in facilitating the use of library collections by students. Practical implications of this research include increasing the accessibility and diversity of library collections, as well as increasing the role of library staff in supporting resource use. This research provides an in-depth understanding of the relationship between the use of library collections and student learning at SMAS Nurul Amaliyah Tj. Morawa, as well as highlighting the importance of the RBL approach in maximizing the benefits of library resources in an educational context.